PEMBERDAYAAN MASYARAKAT DI NAGARI LUMPO KABUPATEN PESISIR SELATAN - Yusrawati Yusrawati; Yulizawati Yulizawati; Lusiana El Sinta Bustami; Aldina Ayunda Insani; Vaulinne Basyir; Hudila Rifa Karmila; Feni Andriani; Erda Mutiara Halida; Fitrayeni Fitrayeni; Uliy Iffah; Miranie Safaringga; Laila Rahmi; Rafika Oktova; Ulfa Farah Lisa; Muhammad Iqbal; Rahmat Syawqi; Syandrez Prima Putra; Liganda Endo Mahata; Elfira Yusri (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Pesisir Selatan Regency is one of the districts with 15 sub-districts with the largest population in IV Jurai District. The number of deaths per year on the South Coast fluctuates. In 2015 the number of infant deaths increased from 6 to 42 people (male 29 and 13 female) from the previous year, AKABA of 47 from 18 in the previous year. There were 16 toddlers with herniated nutrition and many pregnant women, namely around 273 pregnant women. Based on a preliminary study conducted by the activity implementation team at the Lumpo Public Health Center, IV Jurai District, Pesisir Selatan Regency, it is known that there is no ultrasound examination facility in pregnancy and prenatal yoga facilities at the Lumpo Puskesmas, besides that there are no similar activities carried out at SD Negeri 016 and MTsN. Nagari Lumpo which is included in the work area of Lumpo Puskesmas. Several tests can be done during pregnancy as an effort to detect early and prevent complications and growth disorders in the fetus. Among others, by monitoring weight gain during pregnancy, conducting general examinations (vital signs), physical examinations that focus on the breasts, abdomen, genitalia with inspection, palpation, auscultation, and percussion, ultrasonography (USG) examinations, and performing supporting examinations in the form of laboratory examination (hemoglobin examination). The result of this activity is an increase in each target group's quality of life by the stages of life after this activity.